Frequency and intensity of exposure mediate resistance to experimental infection with the hookworm, Ancylostoma ceylanicum - Davey, Dylan (2012)
Hookworms are bloodfeeding intestinal nematodes that are a major cause of anemia in resource-limited countries. Despite repeated exposure beginning in early childhood, humans retain lifelong susceptibility to infection without evidence of sterilizing immunity. In contrast, experimental infection of laboratory animals is typically characterized by varying degrees of resistance following primary infection, although the mechanisms underlying this phenomenon remain unknown. In this study, hamsters subjected to a single drug-terminated infection with 100 third stage hookworm larvae were confirmed to be resistant to pathological effects following a subsequent challenge. In a second experiment, hamsters infected twice-weekly with 10 third stage larvae (low inoculum) exhibited clinical and parasitological evidence of continued susceptibility, while those given 100 L3 (high inoculum) developed apparent resistance within 3 days following the initial exposure. The kinetics of parasite-specific IgA, IgM, and IgG antibody production varied by group, which suggests that the humoral immune response to hookworm infection is stimulated by the nature (frequency and intensity) of larval exposure. These results suggest that intermittent low-inoculum larval exposure, which is characterized by prolonged susceptibility to infection, may serve as a more representative model of human hookworm disease for studies of pathogenesis, as well as drug and vaccine development.